On Beggars, “Bettlers” and Yearning in the Works of Rabbi Nachman of Breslev, Mendele Mocher Sforim and Shmuel Yosef Agnon - Chacham, Ronit (MiKAN, 2016)
This essay examines the characteristics of fictional beggars in three pieces: The Tale of Seven Beggars by Rabbi Nachman of Breslav (1810), Fishke the Lame by Shalom Yaacov Abramowitch (Mendele Mocher Sforim, 1888) and Vehaya Ha’akov Lemishor (And the Crooked Shall be Made Straight) by Shmuel Yosef Agnon (1912). Rabbi Nachman called his beggars “bettlers”, for whom begging was a religious practice: they begged to reach redemption. This essay attempts to demonstrate the ways both Abramowitch and Agnon refer to and correspond to the beggars of Rabbi Nachman, and thus to insist that in spite of the obvious differences, the Hassidic-Kabbalistic context is crucial for understanding the works of the other two writers. Rabbi Nachman’s wandering bettlers are the quintessential signifiers of exile - of the detachment from ‘The Place’ (Hamakom), from the sacred. As the article argues, for both Agnon and Abramovitz (in different ways) the beggars represent the yearning for redemption that is neither territorial nor historic; they experience being in a ‘non-place’, which is the only place from which one can grasp the meaning of redemption. Reading the three stories together opens up the option for a non-secular interpretation, one that was denied by Modern Hebrew literature.